Pemisahan Senyawa Terpenoid Ekstrak n-Heksan Daun Kaembu-Embu (Blumea balsamifera) Menggunakan Kromatografi Kolom Gravitasi - Andi Darmawansyah; Nurlansi; Haeruddin (Sains: Jurnal Kimia dan Pendidikan Kimia, 2023)
Terpenoids are a group of hydrocarbons that are widely found in plants, mainly contained in their sap and cell vacuoles. Identification and separation of terpenoid compounds can be carried out using thin layer chromatography (TLC) and gravity column chromatography. This study aims to determine the separation process of terpenoid compounds and to determine the group of n-hexane fractions resulting from column chromatography separation that are positive for terpenoids in kaembu-embu (Blumea balsamifera.) leaves. As much 100grams of fine sample of kaembu-embu (Blumea balsamifera) leaves were macerated using 96% n-hexane solvent, for 5x 24 hoursand obtained extract as much as 8.4 grams after evaporation. The results showed thatThe results of the separation of the n-hexane fraction of kaembu-embu (Blumea Balsamifera) leaf using thin layer chromatography (TLC) contained 9 types of compounds and The n-hexane fraction group was obtained with the column yielding 104 fractions, and the TLC results showed that the terpenoids had an Rf value of 0.30 up to and including 0,80.